A meta-analysis of serum uric acid and diabetic nephropathy risk in type 2 diabetes - Zhao, Jing; Zhao, Lingzhu (Frontiers in Endocrinology, 2026)
ObjectiveTo explore the correlation between serum uric acid (SUA) levels and the risk of diabetic kidney disease (DKD) in patients with type 2 diabetes mellitus (T2DM), and to evaluate the potential clinical implications of uric acid-lowering interventions.MethodsRelevant studies on the relationship between serum uric acid levels and the risk of DKD in patients with type 2 diabetes mellitus were collected by systematically searching databases such as PubMed, Web of Science, and Cochrane Library. The quality of the included studies was evaluated using the Cochrane risk-of-bias assessment tool, and Meta-analysis was performed using RevMan 5.3 software. The primary outcome indicators included the incidence of DKD, the odds ratio (OR) and 95% confidence interval (CI) of the relationship between serum uric acid levels and the risk of DKD.ResultsAfter retrieval and screening, 8 randomized controlled trials (RCTs) (with a sample size of 491) were included in the Meta-analysis. The results showed that the estimated glomerular filtration rate (eGFR) in the hyperuricemia group was lower than that in the normal group (MD = 4.40, 95% CI [0.66, 8.14], P = 0.02), with low heterogeneity; the risk of DKD was significantly increased (OR = 1.85, 95% CI [1.52, 2.26], P<0.001), with moderate heterogeneity (I²=49%). Sensitivity analyses confirmed the robustness of these findings, though the limited sample size and moderate heterogeneity suggest caution in generalizing the results.ConclusionElevated serum uric acid levels are significantly associated with an increased risk of DKD in patients with type 2 diabetes mellitus. Monitoring serum uric acid levels may help to identify high-risk individuals for DKD at an early stage and provide a reference for clinical intervention.